Preparation, characterization, and preliminary pharmacokinetic studies on complex of zerumbone with hydroxypropyl-ß-cyclodeetrin - Mohammad Eid, Eltayeb Elamin (2012)
Zerumbone (ZER) is a mono-sesquiterpene compound derived from ginger zerumbet smith. It has been reported that, ZER showed a significant activity in both in vivo/in vitro studies for different types of cancers such as cervical, colon, liver and breast cancer. To facilitate the in vivo characterization of ZER, a reversed-phase HPLC and UPLCMS/MS methods were developed and validated according to International Conference on Harmonisation of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) and Food and Drug Administration (FDA) guidelines. Due to the high lipophicity (logP > 5) and very limited water solubility of ZER, the bioavailability needs to be increased so that high blood levels can be obtained for moderate doses. In addition low water solubility contribute to its high protein binding that will leads to low therapeutic free ZER concentration and further successive doses will be imposed for the cancer therapy that will not preferable in clinica environment, and preclude intravenous (i.v.) loading as well. Therefore, solubility and stability of ZER are essential physico-chemical properties that must be proved in early stages of drug development process. Hydroxypropyl-β-cyclodextrin (HPβCD) was used in this study to increase the water solubility of ZER as well as its stability. The solubility of ZER was increased > 100 folds by 0.05M HPβCD in water. The ZER/ HPβCD complexes were characterized by phase solubility diagram, in which an AL –isotherm type was investigated. The thermodynamic parameters: enthalpy change (ΔH°), entropy change (ΔS°) and Gibbs free energy (ΔG°) of the complexes were determined in the temperatures range (293- 298 °K) using Van’t Hoff equation. Differential scanning calorimetry (DSC) was used to confirm the formation of the inclusion complexes. Fourier Transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD) and 1H, 13C nuclear magnetic resonance (NMR) were also used to estimate the stoichiometry of the complexes. Molecular mechanics (MM) was used to further scrutinize the mechanism of complexation between ZER and HPβCD, using theoretical semi-emprical calculation PM6. Pure ZER and ZER/ HPβCD complex were found to decompose with acid, base, oxidation and reduction; however, ZER/ HPβCD complex was stable in dry heat compare with pure ZER that decomposed completely. The in vitro dissolution study of ZER from the complex was follow first order kinetics that is independent of concentration, as well as Hugchi model kinetics. The second objective of the study was to determine the parenteral dosage form of ZER through in vivo studies. ZER suspended in carboxymethyl cellulose sodium salt (CMC) was for intraperitoneal while ZER/HPβCD inclusion complex for intravenous application. New Zealand white rabbits, Sprague-Dawley rats and BALB/c mice were dosed with ZER or ZER/ HPβCD complex at equivalent doses of 10, 20 and 40 mg ZER/kg body weight respectively. The study showed that ZER/HPβCD complex has improved the pharmacokinetic parameters over pure ZER. Thus the aqueous parenteral dosages of ZER are best achieved through the use of HPβCD in a complex form. The allometric scaling approach is analyzed and the predictive performance for this scaling method in estimating human systemic clearance, volume of distribution , area under the curve and plasma half-life is evaluated. The results show that the formulation of zerumbone in hydroxypropyl-β-cyclodextrin as an intravenous preparation has a good correlation between the animal species and human pharmacokinetics based on the species body weight.